2019
DOI: 10.1038/s41380-019-0614-y
|View full text |Cite
|
Sign up to set email alerts
|

Genetic risk for major depressive disorder and loneliness in sex-specific associations with coronary artery disease

Abstract: Major depressive disorder (MDD) and loneliness are phenotypically and genetically correlated with coronary artery disease (CAD), but whether these associations are explained by pleiotropic genetic variants or shared comorbidities is unclear. To tease apart these scenarios, we first assessed the medical morbidity pattern associated with genetic risk factors for MDD and loneliness by conducting a phenome-wide association study in 18,385 European-ancestry individuals in the Vanderbilt University Medical Center bi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
2
1

Relationship

5
5

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 48 publications
(86 reference statements)
1
34
0
Order By: Relevance
“…Fourth, we found that the two factors differ substantially in their associations with human well-being and disease. Our results expand upon recent phenome-wide association studies of genetic risk for major depressive disorder 33 and schizophrenia 34 , expanding the list of complex traits and medical phenotypes associated with mood and psychotic psychopathology. We also identified an interesting pattern of results in our genetic correlation and phenome-wide association analyses, where the factor comprising more common forms of mood disturbance (F1) had broader and often stronger negative associations with socioeconomic and health-related outcomes than the factor comprising rarer forms of serious mental illness (F2).…”
Section: Discussionsupporting
confidence: 67%
“…Fourth, we found that the two factors differ substantially in their associations with human well-being and disease. Our results expand upon recent phenome-wide association studies of genetic risk for major depressive disorder 33 and schizophrenia 34 , expanding the list of complex traits and medical phenotypes associated with mood and psychotic psychopathology. We also identified an interesting pattern of results in our genetic correlation and phenome-wide association analyses, where the factor comprising more common forms of mood disturbance (F1) had broader and often stronger negative associations with socioeconomic and health-related outcomes than the factor comprising rarer forms of serious mental illness (F2).…”
Section: Discussionsupporting
confidence: 67%
“…Genotyping and quality control of this sample have been described elsewhere. 41 A logistic regression model was fitted to each of 1335 case or control phenotypes that had at least 100 cases to estimate the odds of each diagnosis given the PRS for cannabis use disorder, after adjustment for sex, median age of the longitudinal electronic health record measurements, and the top ten ancestral principal controls. To explore whether pleiotropic effects of the PRS for cannabis use disorder were mediated by smoking behaviours, we did two phenotype-wide association study (PheWAS) sensitivity analyses: a PheWAS on summary statistics of cannabis use disorder that had been conditioned on the top smoking initiation loci using mtCOJO, 35 and a PheWAS using a diagnosis of tobacco use disorders as an additional covariate in the regression model, which is a conservative over-correction given the extremely high comorbidity expected between cannabis use disorder and tobacco use disorder.…”
Section: Methodsmentioning
confidence: 99%
“…For each of the unrelated genotyped individuals of European ancestry from BioVU, we computed polygenic risk scores (PRS) for POU using the PRS-CS “auto” version [ 34 ]. Genotyping and quality control for this cohort have been extensively described [ 35 , 36 ].…”
Section: Methodsmentioning
confidence: 99%